“Going to the Dogs”: Canid Ethology and Theological Reflection - Howell, Nancy R. (Zygon, 2006)
Abstract. Theological reflection often treats animals in the very broadest terms and establishes a dramatic difference between humans and animals. Empirical observations, however, describe animals and their relationship to humans in more nuanced ways. Marc Bekoff's science, which integrates ethology and ecology, generates a view of the complex social behaviors of animals and entails observations about difference. Dialogue with Bekoff's sensitive awareness of animal behavior is the occasion to construct a theology of nature that is better informed about diversity among animals and differences within and among species.